Epitope-Specific Tolerance Modes Differentially Specify Susceptibility to Proteolipid Protein-Induced Experimental Autoimmune Encephalomyelitis - Wang, Lei; Winnewisser, Julia; Federle, Christine; Jessberger, Gregor; Nave, Klaus-Armin; Werner, Hauke B.; Kyewski, Bruno; Klein, Ludger; Hinterberger, Maria (Frontiers in Immunology, 2017)
Immunization with myelin components can elicit experimental autoimmune encephalomyelitis (EAE). EAE susceptibility varies between mouse strains, depending on the antigen employed. BL/6 mice are largely resistant to EAE induction with proteolipid protein (PLP), probably a reflection of antigen-specific tolerance. However, the extent and mechanism(s) of tolerance to PLP remain unclear. Here, we identified three PLP epitopes in PLP-deficient BL/6 mice. PLP-sufficient mice did not respond against two of these, whereas tolerance was ‘leaky’ for an epitope with weak predicted MHCII-binding, and only this epitope was encephalitogenic. In TCR transgenic mice, the ‘EAE-susceptibility-associated’ epitope was ‘ignored’ by specific CD4 T cells, whereas the ‘resistance-associated’ epitope induced clonal deletion and Treg induction in the thymus. Central tolerance was AIRE-dependent and required expression and presentation of PLP by thymic epithelial cells (TECs). TEC-specific ablation of PLP revealed that peripheral tolerance, mediated by DCs through recessive tolerance mechanisms (deletion and anergy), could largely compensate for a lack of central tolerance. However, adoptive EAE was exacerbated in mice lacking PLP in TECs, pointing towards a non-redundant role of the thymus in dominant tolerance to PLP. Our findings reveal multiple layers of tolerance to a CNS autoantigen that vary among epitopes and thereby specify disease susceptibility. Understanding how different modalities of tolerance apply to distinct T cell epitopes of a target in autoimmunity has implications for antigen-specific strategies to therapeutically interfere with unwanted immune-reactions against self.